Bibliographical Principles and George Eld's Quarto of Shakespeare's Sonnets. (18th June 2019) - Jackson, MacDonald P
Abstract: In an article published in The Library in 1975, MacD. P. Jackson sought to demonstrate that George Eld's Quarto (1609) of Shakespeare's Sonnets was set by two compositors, who punctuated the text in strikingly different ways. Although this finding has been endorsed by most editors, Carl D. Atkins asserted in 2007 that it is 'not supportable by the bibliographical facts', and the competing views have been recorded, in a non-committal manner, by Francis X. Connor in The New Oxford Shakespeare (2017). The present note outlines the evidence supporting the original conclusion, appraises Atkins's counter-arguments, and shows that some of Atkins's data undermine his own case. Bibliographical principles governing compositor determination are discussed. It is acknowledged that editors preparing old-spelling texts should retain the Quarto's punctuation wherever it is not plainly erroneous by the liberal conventions of its time. But much of it cannot be Shakespeare's.